Phytochemistry and Pharmacological Analysis of Gerbera Jamesonii: A Review - Gupta, Siddhi; Singh, Manish; Kal, Purshottam; Dadupanthi, Priyanka; Bhardwaj, Harsh; Maheshwari, Raaz K. (European Journal of Applied Sciences, 2025)
One high-profile ornamental plant in the Asteraceae family that has come under intense scientific attention is Gerbera jamesonii A reg. Hook.f., which now is being studied not only owing to its horticultural and economical potential but also owing to its dense phytochemical and pharmacological profile. In addition, the plant contains abundant flavonoid, coumarin, phenolic acid, and sterol and exhibits strong antioxidant, anti-inflammatory, anti-microbe, and anti-proliferative effects, highlighting the potential of using the plant in pharmaceutical concern development. New developments in floriculture, including nanotechnology-based curing, trendy and beneficial biostimulatory microorganisms, and optimisation of long-term light qualities, have augmented stress persistence, growth, and after-harvest permanence, further enforcing the commercial interest of the vegetable. Nevertheless, additional limitations to translational opportunities, including the unclinical validation, standard protocols, and mechanistic research, are hindering. Based on a synthesis of the phytochemical, pharmacological, and horticultural data, this paper presents a case that G. jamesonii is a viable agricultural crop suitable for ornamental use and a potential wellspring of bioactivity portfolios in agricultural and biomedical innovation.